Level of awareness about pregnancy danger signs among pregnant women attending antenatal care, Chidambaram - Felix A., John William; R., Devi; M., Manobharathi (International Journal Of Community Medicine And Public Health, 2018)
Background: Delay in seeking health care is one of the key factors leading to maternal death, which can be associated with lack of awareness about obstetric danger signs. So, it is essential that pregnant women should be aware about danger signs of obstetric complications so that they can seek timely healthcare. This study aims to assess level of awareness about danger signs of pregnancy among ANC attendant pregnant women and to assess the factors associated with it. Methods: A descriptive cross-sectional study was done among 170 pregnant women. The level of awareness about danger signs were assessed by administering pre tested proforma to the participants. The collected data was entered in Microsoft excel 2010 and the data was compiled analysed usingSPSS version 21. Results: Of the total participants, only 29.3% had good awareness and about 69.3% had fair awareness about danger signs of pregnancy. It was found that increasing maternal age had significant association with awareness about danger signs whereas other factors like type of family, education, residence, order and duration of pregnancy, number of an visits, previous risk pregnancies had no significant association with level of awareness about danger signs. Conclusions: Level of awareness about danger signs among pregnant women was average. Thus, provision of health education, empowering women and improving the quality of health services can be the recommended interventions.